Problems Encountering MA Students when Translating the Headlines of Newspapers from English into Standard Arabic - Hanaqtah, Mohammad; Falahy, Thanaa Hindi Salih Al–; Abu-Taleb, Yasmeen (International Journal of Membrane Science and Technology, 2023)
News headline writing has it’s own lexical, rhetorical, grammatical, and type of written discourse features different from other types of text. Because of their lexical, stylistic, special grammar, and cultural specificity students find them difficult to translate. The objective of this paper is to study the difficulties that encounter M.A. students when translating newspaper headlines from English into Arabic. To achieve the goal of the study a group of 40 M.A. students was selected. The students were enrolled in M.A. programs in three Jordanian Universities. The researchers designed a translation test that contained 30 news headlines to be translated from English into Arabic. The results revealed that the students encountered many difficulties in translating news headlines. These difficulties were attributed to the use of literal translation, inability to choose the correct equivalences, and unawareness of the structure, style, and features of news headlines. Engaging students in training courses as well as expanding their knowledge of the target culture was highly recommended.